2018
DOI: 10.18517/ijaseit.8.6.3903
|View full text |Cite
|
Sign up to set email alerts
|

Inner-Canthus Localization of Thermal Images in Face-View Invariant

Abstract: Inner-canthus localization has played an essential role in measuring human body temperature. This is due to the theory that human core body temperature can be measured in the inner-canthus. Such measurement is useful for mass screening since it is non-contact, non-invasive and fast. This paper presents an algorithm that has been developed to locate the inner-canthus. The algorithm proposed a robust method in various face-view, i.e., frontal, sided and tilted. The algorithm consisted of: face segmentation, dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The face must not wearing glasses since the inner-canthus would be covered and infrared could not transmit through glass. Images were acquired using thermal infrared camera with locked range of temperature of 26 C -37 C. Face detection algorithm for infrared images has been explained in [8] which used human temperature as threshold. The seg-mented face from background is shown in Fig.1(a).…”
Section: Methodsmentioning
confidence: 99%
“…The face must not wearing glasses since the inner-canthus would be covered and infrared could not transmit through glass. Images were acquired using thermal infrared camera with locked range of temperature of 26 C -37 C. Face detection algorithm for infrared images has been explained in [8] which used human temperature as threshold. The seg-mented face from background is shown in Fig.1(a).…”
Section: Methodsmentioning
confidence: 99%
“…However, this algorithm lacks reliability in cases of longer face height and in cases of neck presence in the image, for example, which resulted in an error in proportions. Accordingly, the eye frame will not be correctly localized, causing incorrect inner canthus detection [ 13 ]. Additionally, Knapik et al, in their paper entitled “Fast Eyes Detection in Thermal Images”, presented a pre-processing image technique that mainly converts the low-dynamic range thermal image into a high-dynamic range image for detail enhancement followed by the use of scale-invariant feature transform (SIFT).…”
Section: Introductionmentioning
confidence: 99%
“…Fitriyah et al [31] detected the inner canthi by finding a collection of blobs, two of which contain the inner canthi, but the results revealed that their knowledge-based criteria falsely identified non-canthi points. Another study [32] located the inner canthi in thermal images of people whose heads were tilted and rotated at different angles, but when eye localization was performed inside the face bounding box, the presence of a subject's neck in the box could affect the system's ability to locate their canthi. Berlincioni et al [33] proposed an automated method for localizing inner canthi in thermal images by using the OpenPose detector to estimate coarse canthi locations which were refined using a 3D Morphable Face Model.…”
Section: Introductionmentioning
confidence: 99%